Origin of an enhanced colossal magnetoresistance effect in epitaxial Nd0.52Sr0.48MnO3 thin films - Prokhorov, V.G.; Nikolaenko, Yu.M.; Levtchenko, G.G.; Svetchnikov, V.L.; Lee, Y.P.; Park, J.S.; Eom, T.W.; Kim, J.M.; Kaminsky, G.G.; Khokhlov, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Nd0.52Sr0.48MnO3 films with the different thickness have been prepared by dc magnetron sputtering on LaAlO3 (001) single-crystalline substrates. A decrease of the film thickness leads to a significant suppression of the ferromagnetic (FM) ordering and the Curie point becomes below the antiferromagnetic (AFM) transition temperature. As this take place, a huge rise of the magnetoresistance ratio from 400 to 60 000% at an applied magnetic field of 5 T is observed. We consider that this new kind of the enhanced colossal magnetoresistance effect is originated from the FM/AFM competition and the collapse of the charge-ordered state at high magnetic field rather than through the regular double-exchange mechanism.